Educational Technology in Teaching Community: Reviewing the Dimension of Integrating Ed-Tech Tools and Ideas in Classrooms - Sk Rezwan Shihab; Nahida Sultana; Abdul Samad; Muhammad Hamza (Green Publisher Indonesia, 2023)
Particularly in light of the COVID-19 epidemic, technology is a catalyst for changing teaching and learning, not just a tool for providing information. This essay aims to examine the three ways that personalization, relevance, and skill development might affect the teaching profession. This research is a qualitative research and library research. The capacity of educators to adapt learning experiences to the needs, interests, and preferences of each student is referred to as personalization. By giving users access to data, material, and the cloud, technology may enable personalization and allow teachers to track student progress, differentiate their lessons, and give feedback. Technology can enable students to take control of their education and choose their own speed and direction. Relevance is the relationship between what students are learning and their personal objectives, ambitions, and aspirations. By establishing blended learning settings that include online and offline activities, real-world challenges, and realistic assignments, technology may increase relevance. Students may engage with classmates and professionals, access materials outside of the classroom, and apply what they have learned in many circumstances with the use of technology. The development of students' skills includes preparing them for the workforce and culture of the twenty-first century. By introducing kids to contemporary technology tools and abilities including coding, programming, physical computing, and computational thinking, technology may promote skill development. Through maker education and STEAM (science, technology, engineering, arts, and mathematics) education, technology can also encourage students to develop their problem-solving, critical thinking, collaborative, and creative skills.